Etnicitet och historia - Berg, Magnus (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1993)
The present article deals with history in its use as a tool in the present day; more precisely, how a group of second-generation Turkish immigrants living in Gothenburg uses Turkish history as a way of indirectly describing itself and its own current ideological standpoints. These self-descriptions are aimed in two directions. The first is directed internally, and its intention is to formulate an understanding of the Turkish group in Sweden today which the group itself can accept. The second self-description is directed externally, and here the intent is to produce a dignified image of the group that can function as a challenge toward and resistance against Swedish stereotypes about Turks. Two rather distinct tendencies can be discerned among the references to Turkish history made within the group. One emphasizes the antiquity of Turkish culture ⁠— it is more ancient and therefore superior to Swedish culture. Significant here is the image of the Turkish village, described as a true gemeinschaft consisting of positive human virtues such as solidarity, generosity, a "natural" religiosity. The other tenddency is characterized by indignant opposition toward what is apprehended as an anti-modern attitude dominant within the group. The desire here is to draw attention to Turkey’s modernistic experiences and to market an idea of historical progress against the continuous disapproval of the unmodern element. In emphasizing this aspect, the group protexts itself against Swedish stereotypes concerning its native country’s cultural backwardness.